THE TRANSFORMATION OF CHINA'S EDUCATION SYSTEM: BETWEEN CONFUCIAN TRADITIONS AND GLOBAL MODERNIZATION - Wei Xiaolong; Ming Yufeng; Jun Jie; Jia Hao (International Journal of Education and Social Science Studies, 2025)
This article explores the dynamic transformation of the education system in China, situated at the crossroads of deeply rooted Confucian traditions and the forces of global modernization. It investigates how Confucian values—such as moral cultivation, respect for authority, and emphasis on academic rigor—continue to shape educational practices and cultural expectations, while simultaneously confronting pressures to adopt innovative pedagogical methods and international standards. The study employs a qualitative approach, analyzing policy documents, educational reforms, and scholarly literature to examine key dimensions including curriculum modernization, technology integration, teacher professional development, rural-urban disparities, and the internationalization of education. Findings reveal a complex interplay between preserving cultural heritage and embracing global competencies, highlighting both achievements and ongoing challenges such as equity gaps and balancing national identity with global engagement. The article concludes that China’s education reform is a continuous process of negotiation between tradition and modernity, aiming to produce learners equipped for the demands of the 21st century while maintaining social cohesion and cultural continuity. This synthesis offers insights into the multifaceted nature of educational change in one of the world’s largest and fastest-evolving education systems.